A Fault Tolerant Control for Sensor and Actuator Failures of an Non Linear Hybrid System - Chalandi Hanene; Ben Slimane Jihane; Ksouri Moufida (Institute of Advanced Engineering and Science, 2018)
We focused in this work on a fault tolerant control of a non linear hybrid system class based on diagnosis method (determine and locate the defects and their types) and on the faults reconfiguration method.In literature we can found many important research activities over the fault-tolerant control of non linear systems and linear Hybridsystems. But it dosen´t exist too many for the non linear hybridsystem.The main idea in this paper is to consider a new approach to improve the reconfiguration performance of the non linear hybrid system by using hammerstein method which is designed to works only for linear systems. This method compensated the effect of the faults and guarantees the closed-loop system stable. The proposed method is simulated with a hydraulic system of two tanks with 4 modes.